2018
DOI: 10.1002/chem.201705657
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Analysis, and Optoelectronic Properties of Diazole‐Functionalized Acenes and Azaacenes

Abstract: Doping heteroatoms into the skeletons of parent acenes can provide more opportunities to construct novel thermally and photostable organic π-conjugated semiconductors. Herein, a family of diazole-decorated acenes (APyS and APySe) and azaacenes (PyP, PyTh, PyPy, PyPh, and PyAP) have been successfully synthesized through the classical reactions. Single-crystal X-ray analyses showed that these as-formed diazole-modified derivatives adopted a twisted topology configuration, whereas the azaacenes display reclining-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 80 publications
1
20
0
Order By: Relevance
“…Azaacenes and their derivatives have been widely investigated due to their unique properties and employed in optoelectronic devices, e. g. as emitters in organic light‐emitting diodes (OLEDs) or in organic field‐effect transistors (OFETs) …”
Section: Introductionmentioning
confidence: 99%
“…Azaacenes and their derivatives have been widely investigated due to their unique properties and employed in optoelectronic devices, e. g. as emitters in organic light‐emitting diodes (OLEDs) or in organic field‐effect transistors (OFETs) …”
Section: Introductionmentioning
confidence: 99%
“…Apparently, BTX easily formed a dimer. Because of intermolecular mismatch arrangement of benzo[ kl ]xanthene unit, there was no π‐π interactions, despite of the distance between them of 3.42 Å ,. The twisted structure and the mismatch intrermolecular packing suppressed the π‐stacking interaction to a certain extent and thus this desired molecule might be chosen as appealing active candidate for organic device.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, py has a pyridine structure, for which the representative UV/VIS curves are shown in Figure 3a. Previous investigations have reported that the pyridine structure can exhibit the interaction of py–py stacking [28,43,44]. Thus, we acquired a UV-VIS absorption spectra for a mixture of bacteriophage, pyrrole, and CA prior to polymerization.…”
Section: Resultsmentioning
confidence: 99%